2006
DOI: 10.1093/ije/dyl083
|View full text |Cite
|
Sign up to set email alerts
|

Widening socioeconomic inequalities in US life expectancy, 1980–2000

Abstract: Between 1980 and 2000, those in higher socioeconomic groups experienced larger gains in life expectancy than those in more-deprived groups, contributing to the widening gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
274
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(305 citation statements)
references
References 15 publications
21
274
2
4
Order By: Relevance
“…Although studies on this issue are rare in the United States, 36 a recent analysis demonstrated increasing disparity in life expectancy between rich and poor Americans. 37 Our comparison of white adults from the United Kingdom and United States revealed a sex difference. American males had greater waist circumference than British men, whether or not adjusted for hip or thigh girth.…”
mentioning
confidence: 81%
“…Although studies on this issue are rare in the United States, 36 a recent analysis demonstrated increasing disparity in life expectancy between rich and poor Americans. 37 Our comparison of white adults from the United Kingdom and United States revealed a sex difference. American males had greater waist circumference than British men, whether or not adjusted for hip or thigh girth.…”
mentioning
confidence: 81%
“…She finds that the top half of the average relative earnings distribution experienced much faster improvements in life expectancy than the bottom half did. Similarly, Singh and Siahpush (2006) conclude that the 2.8 years gap in life expectancy between the top and bottom decile deprivation index groups in the U.S. population in 1980-82 had widened to 4.5 years in 2000. In the paper closest to ours, Tarkiainen, Martikainen, Laaksonen, and Valkonen (2012) show that differences in mortality across household disposable income groups have widened dramatically in Finland between 1988 and 2007.…”
Section: Related Literaturementioning
confidence: 93%
“…The health conditions of poorer population segments tend to be worse than those of richer population segmentsfor economic reasons such as spending on health care and/or for reasons of social or psychic deprivation. There is evidence to this effect from selected case studies, typically for high-income countries, including the well-known Whitehall studies in the United Kingdom (see, e.g., Marmot 2003;Anderson and Marmot 2012) and for the United States (Singh and Siahpush 2006). Comparable data do not exist for a panel analysis.…”
Section: Data and Preliminary Evidencementioning
confidence: 99%